2012
DOI: 10.1021/nn3051677
|View full text |Cite
|
Sign up to set email alerts
|

pH Tuning of DNA Translocation Time through Organically Functionalized Nanopores

Abstract: Controlling DNA translocation speed is of critical importance for nanopore sequencing as free electrophoretic threading is far too rapid to resolve individual bases. A number of promising strategies have been explored in recent years, largely driven by the demands of next-generation sequencing. Engineering DNA-nanopore interactions (known to dominate translocation dynamics) with organic coatings is an attractive method as it does not require sample modification, processive enzymes, or complicated and expensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 21 publications
7
145
0
1
Order By: Relevance
“…For example, modifications to solid-state nanopores have included adjusting the nanopore diameter to increase friction [58][59][60], modulating the nanopore surface charge with laser light [61], functionalizing the nanopore with hydrogen-bonding molecules [62] or coating it with a lipid bilayer [63], and altering the properties of a pH-responsive organic nanopore coating [64]. Additional methods have been proposed, including local heating of a gold layer surrounding the nanopore to stretch the DNA [65,66] and ratcheting of nucleotide strands through introduction of a third electrode [67,68].…”
Section: The Nanoporementioning
confidence: 99%
“…For example, modifications to solid-state nanopores have included adjusting the nanopore diameter to increase friction [58][59][60], modulating the nanopore surface charge with laser light [61], functionalizing the nanopore with hydrogen-bonding molecules [62] or coating it with a lipid bilayer [63], and altering the properties of a pH-responsive organic nanopore coating [64]. Additional methods have been proposed, including local heating of a gold layer surrounding the nanopore to stretch the DNA [65,66] and ratcheting of nucleotide strands through introduction of a third electrode [67,68].…”
Section: The Nanoporementioning
confidence: 99%
“…26 Furthermore, it is well known in the literature that the characteristics of polymer translocation through nanopores are dramatically influenced by pore-polymer interactions. 12,[27][28][29][30][31][32][33][34][35] Using simulations in two dimensions, Ikonen et al have shown that the attractive pore-polymer interactions significantly induce resonant activation. 36 Stochastic resonance has been realized 37,38 in several practical situations such as electronic circuits, bistable ring-lasers, sensory processes of crayfish, and voltage-dependent ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins such as RecA from Escherichia coli form filaments around the DNA that slows DNA transport and prevents its folding (26,34,35), although this approach inherently masks chemical information contained within the DNA, such as the presence of DNA chemical modifications (7,36) or small bound drug/reporter molecules (37)(38)(39)(40). Explorations of the effects of parameters such as the electrolyte viscosity (41,42), salt type (43,44), membrane material (45,46), applied pressure (47,48), and chemical composition inside (49)(50)(51)(52) and outside (53) the pore have yielded only moderate DNA retardation factors.…”
Section: Introductionmentioning
confidence: 99%